Guidelines on national inventory of village forests - Singh, K.D. (Center for International Forestry Research, 2000)
This report presents guidelines which provide a basis for planning and implementation of nation wide village forest inventories integrated with or independent of a national forest inventory. It provides coverage of survey problems arising from the variety of spatial distribution conditions of forests and trees under village management landscapes. The guidelines cover survey planning, survey design, survey implementation and survey analysis /evaluation. The main issues in the planning phase such as specification of expected results, statistical outputs and precision of results are discussed. The emphasis in survey design is on definition of survey area, construction of a sampling framework and use of remote sensing data to supplement the field observations. In survey implementation, data must be collected in a consistent manner and with a minimum of bias or non-sampling errors. The importance of good management of the field survey team(s) is stressed. The data processing phase of an inventory includes establishment of an error-free database, analysis and reporting. For the purposes of a national inventory, it is essential that the database and results are well documented and archived so that the planning at the next cycle of inventory can profit from the past experience and the survey conducted in a consistent manner to estimate changes. Survey evaluation, a retrospective phase not included in most inventories, is considered important in village forest inventories for which the knowledge base to guide inventory planning is very limited.